First Lithuanian map of Suvalkija - Girkus, Romualdas; Lukoševičius, Viktoras (Geodesy and Cartography, 2012)
After a lengthy period of search, with the help of Dr. N. Lietuvninkaite, M1:252 000 Suvalkijos map, published by B. K. Balutis in 1915 in the USA was located in the archives of KTU Rare Books Department, Cartography division. However, no facts were found regarding its design in B. K. Balutis fund in the Lithuanian Emigration Institute. The search itself looked hopeless because of wrong information in Lithuanian Encyclopaedia describing the period between two World Wars. It was stated there that because of World War 1 the map was never published. Thus, this is the first publication including its description. Also, illustrations for the article present the fragments of the Povilas Matulionis map ‘‘Mountainousness and Inclination Map of Lithuania and Outskirts“, 1924 and of the map of Suvalkija province, 1905.Article in Lithuanian.Pirmasis Lietuviškas Suvalkijos žemėlapisSantrauka. Po ilgo paieškos laikotarpio, dr. N. Lietuvninkaitei padedant, KTU bibliotekos Retų knygų skyriaus kartografiniame archyve aptiktas 1915 m. JAV išleistas B. K. Balučio M 1:252 000 Suvalkijos žemėlapis. Lietuvių išeivijos instituto B. K. Balučio fonde žemėlapio sudarymo medžiagos nerasta. Paieška atrodė beviltiška dėl tarpukario Lietuviškosios enciklopedijos klaidinančios informacijos, kad prasidėjus Pirmajam pasauliniam karui žemėlapis nebuvo išleistas, tad aprašomas ir publikuojamas pirmą kartą.Reikšminiai žodžiai: Lietuvos žemėlapiai, varstinė sistema, gubernija, pavietas, mozūrai.First published online: 03 Aug 2012